Environmental conditions and actual distribution of fish resources in the Lower Musi River South Sumatra, Indonesia - Agnes Puspitasari Sudarmo; Mirna Dwirastina; Yoga Candra Ditya (Fisheries and Aquatic Sciences)
The study was conducted in the downstream area of the Musi River, namely Salah Nama and Sungsang Islands, South Sumatra, Indonesia. Salah Island is a flooded swamp area and is influenced by the ebb and flow of the Musi River. While Sungsang is the estuary area of the Musi River. The aquatic environment is closely related to fish resources in these waters. Primary and secondary data collection was carried out in 2007–2023. This study used survey and literature study methods and fish sampling using the purposive sampling method with enumerators as intermediaries in the recording. Water quality sampling was carried out in situ and laboratory analysis. The analysis of water quality data used was PCA which was adjusted to the research assumptions. The focus of the study was to determine the relationship between the aquatic environment and the distribution of fish resources on Salah Nama Islands and Sungsang, South Sumatra. The results showed that temperature, brightness, dissolved oxygen, N-Total, P-Total, salinity, and pH were still in good condition for fish life. While the actual data on the distribution of fish resources in 2007–2023 showed a decrease in the number of species and families, namely 112 species to 23 species and 21 families to 20 families, the dominant family is Cyprinidae. The decrease in the diversity of fish resource species in the Lower Musi River tends to be caused by fishing activity behaviour and water conditions.